Selective value of environmentally distant samples of buckwheat of the National Collection of Ukraine - Тригуб, О. В.; Ляшенко, В. В.; Бараболя, О. В. (Scientific Progress & Innovations, 2018)
Buckwheat is extremely receptive to adapt to the culture that was spread through the territory of most regions of the world (Eurasia, Australia, Africa, South and North America), and practically reached the limits of agriculture. It can be grown everywhere, where the frost-free period lasts more than 60 days and the average daily air temperature exceeds 17–18 0C, and the amount of lunar rainfall is 50–60 mm [3]. This geographical distribution led to a significant difference between the samples grown in different regions of the world, which was formed under the influence of environmental factors and served in the early stages as an adaptive mechanism. The article presents the results of the study of the buckwheat collection material of the National Collection of Ukraine of different ecological and geographical origin by economic and selection-valuable indicators. The distribution of the gene pool of the study group is carried out depending on the ecological suitability of the varieties and forms. Of the variety, the most valuable samples are selected, which can be recommended as sources of valuable attributes with increased parameters of yield, plant productivity, and large-grain yield, which is combined with high grain leveling; which has a significant number of inflorescences and high fertility (lacustrine), genetically determined parameters of the height of the plant and the number of nodes from the branching zone; it is characterized by the controlled duration of the growing season, coupled with the achievement's friendliness, the type of plant growth, resistance to shedding and sinking of the fruits; and it also has increased parameters of drought resistance and heat resistance, etc. Of great value is the wide representation in the selected material of samples of various ecological and geographical groups, which allows selection by one sign or another not to narrow the genetic basis of newly created varieties, to search among the source forms the most rational combination of features and properties. This is especially valuable in the conditions of rapid change of environmental factors, as well as the introduction of new directions of use of buckwheat and, as a result, search of alternative sources with a complex of non-typical for a modern high-grade material characteristics among the gene pool.